Adsorption of Vanillin by an Anisole‐Modified Hyper‐Cross‐Linked Polystyrene Resin from Aqueous Solution: Equilibrium, Kinetics, and Dynamics. Issue 1 (1st May 2012) - Jin, Xiaoying; Huang, Jianhan
Abstract A type of anisole‐modified hyper‐cross‐linked polystyrene (PS) resin, named HJ‐J00, HJ‐J04, HJ‐J08, HJ‐J10, and HJ‐J12, was synthesized, characterized, and evaluated for adsorption of vanillin from aqueous solution in this study. These resins were prepared from macroporous chloromethylated PS by adding different quantities of anisole in the Friedel–Crafts reaction; they had different adsorption selectivity toward β‐naphthol and vanillin from aqueous solution, and HJ‐J08 held the largest adsorption capacity toward vanillin. The isotherms of vanillin on HJ‐J08 were measured and fitted by the Freundlich equation, and isosteric adsorption enthalpies were calculated according to the Clausius–Clapeyron equation. The second‐order rate equation was shown to be suitable for fitting the kinetic data, and the intraparticle diffusion was the rate‐controlling step in the first stage. The breakthrough point of HJ‐J08 toward vanillin was 75 BV (bed volume; 1 BV = 10 mL) with the initial concentration of 1000 mg/L, and a flow rate of 6 BV/h, exhibiting an excellent adsorption property toward vanillin. © 2012 Wiley Periodicals, Inc. Adv Polym Techn 32: E221–E230, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/adv.21268